2021
DOI: 10.21037/atm-21-5822
|View full text |Cite
|
Sign up to set email alerts
|

Liver segmentation in CT imaging with enhanced mask region-based convolutional neural networks

Abstract: Background: Liver segmentation in computed tomography (CT) imaging has been widely investigated as a crucial step for analyzing liver characteristics and diagnosing liver diseases. However, obtaining satisfactory liver segmentation performance is highly challenging because of the poor contrast between the liver and its surrounding organs and tissues, the high levels of CT image noise, and the wide variability in liver shapes among patients.Methods: To overcome these challenges, we propose a novel method for li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Weston et al (2020) [ 25 ] established a liver segmentation method based on the CNN algorithm, and the results showed that the Dice value of this method for segmenting liver CT images was 0.79. Chen et al (2021) [ 26 ] optimized the model based on the FCN algorithm and applied it to liver segmentation. The results showed that the Dice value of this method for segmenting liver CT images was 0.742.…”
Section: Discussionmentioning
confidence: 99%
“…Weston et al (2020) [ 25 ] established a liver segmentation method based on the CNN algorithm, and the results showed that the Dice value of this method for segmenting liver CT images was 0.79. Chen et al (2021) [ 26 ] optimized the model based on the FCN algorithm and applied it to liver segmentation. The results showed that the Dice value of this method for segmenting liver CT images was 0.742.…”
Section: Discussionmentioning
confidence: 99%
“…SFF-Net (Spatial Feature Fusion Convolutional Network) was proposed by Liu et al [41]. Chen et al [42] combine enhanced Mask R-CNN and graph-cut for liver segmentation.…”
Section: Related Workmentioning
confidence: 99%
“…Chen, Xiaowen et al suggested a Mask R-CNN technique that outperformed the conventional Mask R-CNN techniques when evaluated using the Dice Similarity Coefficient and Medicinal Image Computing and Computer-Assisted Intervention (MICCAI) metrics [15]. Chen, Lei et al have implemented ASD, MSD, VOE, and RVD all improved using an adversarial training strategy from 27.8 to 21, 147 to 124, 0.52 to 0.46, and 0.69 to 0.73, proving the effectiveness of the suggested approach.…”
Section: Related Workmentioning
confidence: 99%